The general principles of law and their implications for the improvement of the administration of justice - Carrillo Rodríguez, Jorge Luis (2018)
In this article, we examine the definitions and characteristics of some general principles of law (abuse of rights, the principle of good faith, the doctrine of actos propios and fraud against the law) and the implications of their applications in the national and international jurisdictional areas.